The Effect of Drill Method on the Achievement of Memorisation of Qs An Naba Qur'an Subjects at Ashqaf Millennial Tahfidz Pondok and Maryam College - Luthfan, Muhammad Arief; Sumin; Muttaqin, Imron (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to determine (1) the achievement of memorising Quran surah An-Naba in Al-Quran subjects in the control class; (2) the achievement of memorising Quran surah An-naba in Al-Quran subjects in the experimental class; (3) the effect of the drill method on the achievement of Quran surah an-naba in Al-Qur'an subjects (4) the effectiveness of the drill method on the achievement of Quran surah an-naba in Al-Qur'an subjects. This type of research is qualitative research with an experimental approach. This research design uses quasi-experiment with nonequivalent type (Pretest and posttest) Control Group Design. The population of this study was the 6th batch of female students at Pondok Tahfidz Millenial Ashqaf and Maryam College. The sampling technique was Probabillity sampling in the form of simple random sampling. Data collection methods using tests and observations. Data analysis using descriptive statistics and t test. The results of this study show: (1) the achievement of memorisation of the control class is known, as many as 50% of the santriwati have not been completed, while 50% of the santriwati who are complete with an average of 76; (2) the achievement of memorisation of the experimental class is known, there are no santriwati who have not been completed, and as many as 100% of the santriwati have been completed with an average of 86.8; (3) there is an effect of using the drill method on the achievement of memorisation of the Quran Surah An-Naba', this is evidenced by the results of the independent sample t-test known significance 0. 060a < 0.05, then H0 is rejected and Ha is accepted, so it can be concluded that there is no significant effect of using the drill method on the achievement of memorising the Quran Surah An-Naba'; (4) the drill method is effectively used on the achievement of memorising the Quran Surah An-Naba', this is evidenced by the number of completed santriwati in the experimental class as much as 100%, and the average of the experimental class is higher than the control class, which is 86.8 while the control class is 76.